Importance of Seaweeds and Extractive Species in Global Aquaculture Production. Issue 2 (3rd April 2021) - Chopin, Thierry; Tacon, Albert G. J.
Abstract: The FAO recently published its biennial State of World Fisheries and Aquaculture up to 2018. The FAO continues to treat the seaweed aquaculture sector as a different category, with separate tables and comments in different sections. As this could lead to a distorted view of total world aquaculture, the statistical information provided by FAO was revisited and data regarding the seaweed aquaculture sector were integrated with data of the other sectors of the world aquaculture production, to reach different conclusions: (1) aquaculture represents 54.1% of total world fisheries and aquaculture production; (2) marine and coastal aquaculture represents 55.2% of total world aquaculture production; (3) seaweeds represent 51.3% of total production of marine and coastal aquaculture; (4) 99.5% of seaweed mariculture production is concentrated in Asia; (5) 8 seaweed genera provide 96.8% of world seaweed mariculture production; (6) 2 seaweed genera are the most produced organisms in mariculture in the world; (7) the value of the seaweed aquaculture sector could be much larger, especially if a monetary value was attributed to the ecosystem services provided by seaweeds; and (8) total extractive aquaculture is slightly larger (50.6%) than total fed aquaculture (49.4%).